Assessing the Learning Environment at the University and the Attitude of Bachelor Students: An Investigation into Hope and Despair - aziz, khanda gharib; Babakr, Helin Xalid (Journal of Linguistics and Social Sciences, 2026)
This research explores the reasons behind students’ disappointment with university learning and demotivation. The study had as its objective to find the psychological and institutional factors on which behavioral attitudes and academic performance of students. A structured questionnaire was used to collect the data from 233 students in Sulaymaniyah, Halabja, and Howler governorates. The data were analyzed by descriptive statistics and factor analysis. The demographic profile revealed that the majority of respondents were females, single and middle-class with parents of low to moderate education. The value of the Kaiser-Meyer-Olkin (KMO) and the Bartlett’s test of sphericity (χ² = 407.634, p < 0.05) showed that the dataset was fit for factor analysis. Four factors with eigenvalues over 1 were extracted, which accounted for 66.19% of the total variance: a lack of goal orientation among students (goal-orientation), a lack of early talent development (early-express-talent), study challenges, and demotivation among students. the results suggest that lack of explicit academic aims, too little developmental and talent nurturing at the early stages, inadequate lesson content and emotional disengagement were the prime reasons for students' dissatisfaction with their lessons. Based on the study, it is recommended that universities adopt project-based learning, early talent development initiatives and psychological counselling to motivate them and enhance the overall academic experience of students